Studi Literatur: Peran Komunikasi Bisnis dalam Mendukung Keberlanjutan (Sustainability) dan Tanggung Jawab Sosial Perusahaan - Raaja Bayu Prasasti; Nailah Bassama; Novita Angreini; Finda Dwi Restiani; Mada Aditia Wardhana (Shofanah Media Berkah, 2026)
Business communication, particularly strategic and corporate communication, plays a vital role in supporting the implementation and integration of sustainability principles and Corporate Social Responsibility (CSR). This study examines the evolution of sustainability narratives in external corporate communication and the role of reporting practices in facilitating strategic integration and image risk mitigation. Through content and discourse analysis of academic literature and corporate reports, this research finds that sustainability narratives have evolved from reactive environmental reporting (1990s), to structured CSR reporting (2000s), towards strategic and future-oriented sustainability reporting (post-2011). This shift is accompanied by an evolution in communication frameworks, moving from an environmental responsibility focus towards a security framework emphasizing safety, stability, and long-term growth. The study also reveals that communication and reporting practices function as instruments of niche construction and strategification to integrate sustainability into core business objectives. Transparency and alignment between narrative and concrete action are key to building stakeholder trust and avoiding greenwashing. The implication is that sustainability communication is performative—it not only describes but also shapes business and social reality.